Using a contemporary archaeology to slow down fast capitalism - McGuire, Randall (2023)
The late twentieth century great intellectual myth is that the twenty-first century was going to awake into a world of “post” phenomena: postindustrial, postcolonial and, the most important, a postcapitalist world. This article builds on previously developed arguments in favor of an archaeological praxis that seek to challenge the status quo and slow down fast capitalism. Although I feel skeptic about big plans to change the world I suggest we can slow somewhat fast capitalism. This is something we can do both in the practice of anthropology and in the world at large. The contradictions of fast capitalism shape the practice of archaeology in the management of cultural resources and in the academia. We can also use archaeology to confront ideological fallacies that support, naturalize and justify growing wealth inequalities. This article proves that archaeology can expose those fallacies in the study of worker’s rights and the U.S. – Mexican border.